Transitional cell carcinoma of the renal pelvis in a dog with combined treatment with unilateral nephrectomy and carboplatin - Ocarino , Natália M.; Souza , Patrícia C.; Boeloni , Jankerle N.; Lavalle , Gleidice E.; Souza , Eliana M.; Pereira , Luiz C.; Serakides, Rogéria (Brazilian Journal of Veterinary Pathology, 2009)
A transitional cell carcinoma of the renal pelvis was diagnosed in a 10-year-old, male German shepherd that presented with a 1-month history of hematuria and weight loss. Unilateral nephrectomy and chemotherapy with carboplatin was applied, but the dog was euthanized five months after the surgery due to metastasis.